Perceived stress as a risk factor of unemployment: a register-based cohort study - Maiken Holm Mæhlisen; Alexander Arndt Pasgaard; Rikke Nørmark Mortensen; Henrik Vardinghus-Nielsen; Christian Torp-Pedersen; Henrik Bøggild (BMC, 2018)
Abstract Background Although unemployment and high levels of perceived stress have been associated in cross-sectional studies, the direction of causation is unknown. We prospectively examined if high levels of perceived everyday life stress increased the risk of subsequent unemployment and further if differences existed between socioeconomic status-groups. Methods We included 9335 18-64-year-old employed respondents of a health survey (North Denmark Health Profile 2010) in which Cohen's Perceived Stress Scale was used to assess the level of perceived stress. Data were linked individually to national administrative registers. Cox proportional hazards model was used to investigate the association between perceived stress quintiles and risk of unemployment during 98 weeks of follow-up. Analyses were further performed in subgroups defined by education and income. Results In total, 224 people (10.4%) of the high stress group became unemployed during follow-up, which was higher than the lower stress groups. After adjusting for gender, age, education and income, the risk of unemployment was 1.64 (95% CI: 1.28;2.11) in the high stress group compared to the low stress group. After adjusting for gender and age, a similar trend was observed across different education levels and among the lower income groups, but no higher risk of unemployment due to perceived stress was found among the higher income groups. However, there was no statistically significant interaction between perceived stress and income level (p = 0.841) or perceived stress and education level (p = 0.587). Conclusion Perceived everyday life stress nearly doubled the risk of subsequent unemployment in a working population. No statistically significant interactions between SES and perceived stress were found. This indicates that stress prevention among the working population should not solely focus on stress in the workplace but also include stress from everyday life.